Association between human cytomegalovirus and periodontitis: A systematic review and meta-analysis (2020)
Background and objective: Human cytomegalovirus (HCMV) has been associated with periodontitis and apical periodontitis. The objective of this systematic review was to evaluate the association between HCMV and periodontitis, and apical periodontitis of endodontic origin. Material and methods: A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines and registered in the International prospective register of systematic reviews (PROSPERO). The search for potential studies was performed in MEDLINE via PubMed, Scopus, and SciELO. A quality assessment of the studies, publication bias analysis, and meta-analysis was performed. The results are presented in odds ratio with 95% confidence interval with the corresponding Forest plot. Sensitivity analysis was performed to evaluate the consistency of the results. Results: Thirty-two studies were included in the quantitative and qualitative analyses. Of these, 26 were in periodontitis patients and 6 in apical periodontitis patients. Forest plot of combined studies revealed significant increased odds for periodontitis when subgingival HCMV was detected (OR 5.31; 95% CI 3.15-8.97). Sensitivity analysis based on quality of the included studies, showed consistent results. In contrast, the odds ratio for apical periodontitis when HCMV was detected from apical lesions was not statistically significant (OR 3.65; 95% CI 0.49-27.10). Conclusions: The results from the meta-analysis indicate that HCMV is significantly associated with periodontitis. In contrast, HCMV infection is not associated with apical periodontitis. © 2020 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd